Evaluasi Program Pemberian Makanan Tambahan pada Balita Gizi Kurang: Evaluation of the Supplementary Feeding Program for Underweight Toddlers - Ida Sofiyanti; Kholifah (Indonesian Journal of Midwifery (IJM), 2026)
The government implemented the Supplementary Feeding Programme (PMT) to address the problem of under-five nutrition. The implementation of the PMT programme needs to be evaluated to improve the quality of implementation so as to achieve the set objectives. This study aimed to evaluate the PMT programme made from Local Food Ingredients at Public Health Center Bojong I in Pekalongan district. The research design was qualitative with phenomenological approach in June 2025. The research subjects consisted of main informants, namely the head of the health centre, nutrition officer, MCH coordinator midwife and village midwife. Triangulation informants consisted of health cadres and mothers of under-fives who were malnourished. The sampling technique used convenience sampling. The research instruments were interview guidelines, recording devices and note-taking tools. Data validity used source triangulation. Data analysis was interactive model. Resources in the implementation of the PMT programme at Public Health Center Bojong I involve the head of the public health center, nutrition officers, MCH coordinator midwives and village midwives. Planning includes determining the number of targets, types and ingredients of food, budget and training for village midwives. Implementation of the PMT programme has been carried out in accordance with the technical guidelines, but still faces obstacles. The immediate result of the PMT programme was increase in body weight of undernourished children. The short-term results of the PMT programme was increased knowledge about toddler nutrition and improved skills in feeding malnourished toddlers. The supplementary feeding programme for undernourished children has been running but there are still obstacles. Innovate PMT by involving nutritionists and cadres with attractive local food ingredients that are appealing to toddlers.   Abstrak Pemerintah melaksanakan program Pemberian Makanan Tambahan (PMT) untuk mengatasi masalah gizi kurang balita. Pelaksanaan program PMT perlu dilakukan evaluasi untuk meningkatkan kualitas pelaksanaan sehingga mencapai tujuan yang ditetapkan. Penelitian ini bertujuan untuk mengevaluasi program Pemberian Makanan Tambahan (PMT) Berbahan Pangan Lokal di Puskesmas Bojong I Kabupaten Pekalongan. Desain penelitian menggunakan kualitatif dengan pendekatan fenomenologi, penelitian dilakukan pada bulan Juni tahun 2025. Subyek penelitian terdiri dari informan utama yaitu kepala puskesmas, petugas gizi, bidan koordinator KIA dan bidan desa. Informan triangulasi terdiri dari kader kesehatan dan ibu balita yang memiliki gizi kurang. Teknik sampling menggunakan convenience sampling. Instrumen penelitian adalah pedoman wawancara, alat perekam dan alat pencatat. Keabsahan data menggunakan triangulasi sumber. Analisis data yaitu model interaktif. Sumber daya dalam pelaksanaan program PMT di Puskesmas Bojong I melibatkan kepala puskesmas, petugas gizi, bidan koordinator KIA dan bidan desa. Perencanaan meliputi menentukan jumlah sasaran, jenis dan bahan makanan, anggaran dan pelatihan bagi bidan desa. Pelaksanaan program PMT telah dilakukan sesuai dengan juknis, namun masih menghadapi kendala. Hasil langsung yang diperoleh dari program PMT adalah peningkatan berat badan balita gizi kurang. Hasil jangka pendek dari program PMT adalah peningkatan pengetahuan tentang gizi balita dan peningkatan ketrampilan dalam pemberian makanan pada balita gizi kurang. Program pemberian makanan tambahan pada balita gizi kurang sudah berjalan namun masih dijumpai kendala. Melakukan inovasi PMT dengan melibatkan petugas gizi dan kader dengan bahan makanan lokal yang menarik dengan cita rasa yang disukai balita.